(untitled) (Global Journal of Medical Research, 2021)
Obesity has been considered a complex and multifactorial disease that has almost affected one-third of the total world#x2019;s population. The present trend related to obesity has revealed that nearly 38% of the adults of the world#x2019;s population will suffer from the issues of being overweight by the year 2030. As per the ICMR-India study in the year 2015, the prevalence rate of obesity in India varies between 11.8% to 31.3%. The risk of cardiovascular diseases is prevalent around the world, and estimated CVD cases in the year 2015 were approximately 422.7 million, causing 17.6 million deaths (32%of global deaths) as per WHO statistics in 2016. The Indian health data of 2017 has revealed that 25.27% of the population have suffered mortality rate due to the occurrence of CVD in India. Hence, the implementation of health programs for identifying the community risk factors for preventing these diseases has evolved.